2023
DOI: 10.3390/cells12070999
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Contribution to Cardiovascular Risk in Chronic Kidney Disease Male Patients

Abstract: Background: Resistin is a molecule that belongs to the Resistin-Like Molecules family (RELMs), the group of proteins taking part in inflammatory processes. Increased resistin concentrations are observed in cardiovascular complications. Resistin contributes to the onset of atherosclerosis and intensifies the atherosclerotic processes. The aim of this study was to investigate the relationship between resistin and cardiovascular (CV) risk in men with chronic kidney disease (CKD) not treated with dialysis. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Increased resistin levels may be involved in the development of malnutritioninflammation states and, consequently, protein-energy wasting, a condition of paramount significance in the context of managing this population [21,22]. Our results corroborate this, showing higher plasma resistin levels in the malnourished group and a positive association with both IL-6 and PG-SGA scores.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Increased resistin levels may be involved in the development of malnutritioninflammation states and, consequently, protein-energy wasting, a condition of paramount significance in the context of managing this population [21,22]. Our results corroborate this, showing higher plasma resistin levels in the malnourished group and a positive association with both IL-6 and PG-SGA scores.…”
Section: Discussionsupporting
confidence: 86%
“…Resistin has gained attention as a potential link between malnutrition, inflammation, and cardiovascular risk in patients with CKD [12,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Our preceding research has further indicated that serum resistin levels could serve as a potential biomarker for aortic stiffness in patients with coronary artery disease (CAD) [ 10 ]. Importantly, resistin levels have recently been shown also to be elevated in CKD patients and could be associated with their higher risk of cardiovascular events [ 11 ].…”
Section: Introductionmentioning
confidence: 99%